The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/2317-6431-2019-2251
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento eletrofisiológico do sistema auditivo central em crianças nascidas pequenas para a idade gestacional

Abstract: RESUMO Objetivo Monitorar o sistema auditivo central de crianças nascidas pequenas para a idade gestacional, por meio da avaliação eletrofisiológica da audição, para verificar a ocorrência de eventuais disfunções neurais nesse sistema. Métodos Estudo longitudinal, cuja casuística foi composta por 23 crianças distribuídas em quatro grupos: 1) grupo de quatro crianças nascidas pequenas para a idade gestacional e a termo; 2) grupo de sete crianças nascidas pequenas para a idade gestacional e pré-termo; 3) grupo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…So, five studies concluded with their investigations that there are changes in neural development in the SGA population influencing the maturation process of the auditory pathway, resulting in abnormalities in the BAEP test. 10 12 16 26 31 On the other hand, five studies 15 25 27 28 29 did not evidence differences between the SGA and AGA groups. These disparities among the results can be justified by some peculiarities among the studies, such as the population studied, differences of methodologies, the type of study used, and the small number of participants in some of the studies.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…So, five studies concluded with their investigations that there are changes in neural development in the SGA population influencing the maturation process of the auditory pathway, resulting in abnormalities in the BAEP test. 10 12 16 26 31 On the other hand, five studies 15 25 27 28 29 did not evidence differences between the SGA and AGA groups. These disparities among the results can be justified by some peculiarities among the studies, such as the population studied, differences of methodologies, the type of study used, and the small number of participants in some of the studies.…”
Section: Discussionmentioning
confidence: 94%
“…These disparities among the results can be justified by some peculiarities among the studies, such as the population studied, differences of methodologies, the type of study used, and the small number of participants in some of the studies. 16,26 Seeking a better understanding of the influence of body proportionality in the process of auditory maturation in SGA newborns, two study groups were analyzed in the first six months of life, one classified as asymmetric and the other as a symmetric group. In the first days of life, there was an alteration in the BAEP in more than 30% in SGA groups, both symmetric and asymmetric, suggesting transitory retro cochlear alterations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations